The work-family interface and the COVID-19 pandemic: A systematic review - Vitória, Beatriz de Araújo; Ribeiro, Maria Teresa; Carvalho, Vânia Sofia (Frontiers in Psychology, 2022)
In an unprecedented fashion, COVID-19 has impacted the work-family interface since March 2020. As one of the COVID-19 pandemic consequences, remote work became widely adopted. Furthermore, it is expected that other pandemics will occur in the future. Hence, this context represents a chance to gain deeper insight into telecommuters’ work and family spheres. Following PRISMA guidelines, the present narrative review aims to synthesise the COVID-19 impact on the work-family interface. Out of 121 screened references, 32 articles that measure at least one of the following variables–work-family conflict (25), work-family enrichment (3), work-family balance (8), and boundary management (21) were included. A thematic analysis using NVIVO12 was conducted, from which eight topics emerged: “paid workload, unpaid workload, and gender”; “well-being and gender”; “job resources, job demands, and gender”; “couples and gender”; “parenting and gender”; “occurrence of work-family enrichment with work-family conflict and gender”; “enforced blurred boundaries, its management, and gender”; “boundary management impact on work-family conflict, work-family enrichment, and work-family balance.” Overall, studies point out that COVID-19 had a complex effect on both work-family conflict and work-family balance, making it difficult to state whether these variables were mitigated or augmented. Findings demonstrated that COVID-19 produced little changes in work-family enrichment. As for the COVID-19 impact on work-family boundary management, individuals had to create new tactics to manage them due to the absence of boundaries between both systems. Besides, due to traditional gendered roles, the COVID-19 health crisis seems to have brought additional hurdles to couples and women. Systematic Review Registration [https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42021278254], identifier [CRD42021278254].